Audit Labor Usage and Fees under Business Risk Auditing - BELL, TIMOTHY B.; DOOGAR, RAJIB; SOLOMON, IRA (Journal of Accounting Research, 2008)
ABSTRACT The adoption of business risk audit (BRA) approaches during the 1990s by several leading audit firms has been the subject of considerable scrutiny and commentary. Under BRA, the auditor responds to the increasing complexity of auditee financial reports by acquiring a deep and comprehensive understanding of the auditee's industry, strategy, business models, and processes—tasks best accomplished by higher‐ranked labor—and by employing this understanding to make audit labor allocations. Using proprietary data for 165 audits conducted in 2002, we investigate three propositions about audit labor use under BRA. First, relative to pre‐BRA benchmarks for the same auditor, we expect BRA audits to use a greater proportion of higher‐ranked labor. Second, we expect engagements with high assessed auditor business risk (ABR), a summary risk assessment that reflects the BRA auditor's rich understanding of the auditee, to be allocated more labor and more higher‐ranked labor than pre‐BRA benchmarks. Third, at all ranks of labor, we expect a positive association between assessed ABR and levels of labor use. We find empirical evidence consistent with these propositions. We also find that total labor use in our sample is only modestly lower than pre‐BRA norms. Analysis of fee data from these engagements suggests that audit fees in 2002 are substantially less than would be expected under pre‐BRA benchmarks. After controlling for audit labor use, both total fees and fees per hour increase with assessed ABR for first‐year auditees but not for continuing auditees. Overall, our results provide evidence on the impact of the BRA audit regime and speak to the likely impact of BRA on audit effectiveness and efficiency.